Increased risk of ischemic heart disease among subjects with cataracts: A population-based cohort study - Hu, Wei-Syun; Lin, Cheng-Li; Chang, Shih-Sheng; Chen, Ming-Fong; Chang, Kuan-Cheng (Medicine (Baltimore), 2016)
Association between cataract and the risk of ischemic heart disease (IHD) development is not completely clear. The primary aim of the study was to evaluate the association between cataract and the risk of incident IHD. The secondary aim was to investigate the subsequent IHD risk of patients with cataracts undergoing cataract surgery. Retrospective data from the Longitudinal Health Insurance Database 2000 (LHID2000) was analyzed. Study participants were composed of patients with cataracts (International Classification of Diseases, 9th Revision, Clinical Modification [ICD-9-CM] code 366) (n = 32,456), and a comparison cohort without the cataracts (n = 32,456) from 2000 to 2010. Cox proportional hazards regression was used to address the hazard ratio (HR) of IHD associated with cataract. Within 12 years of follow up, the overall incidence rates of IHD were 24.2 per 1000 person-years in the cataract cohort and 18.2 per 1000 person-years in the noncataract cohort with an adjusted hazard ratio (aHR) of 1.35 (95% CI = 1.29-1.41; P < 0.001). Furthermore, the cataract patients undergoing cataract surgery were associated with a higher risk of IHD compared with those cataract patients without surgery (aHR = 1.07, 95% CI: 1.01-1.14; P < 0.05). Our finding suggested that patients with cataracts are at an increased risk of subsequent IHD development.